Alison Light -- Inside history : from popular fiction to life-writing - Light, Alison, 1955- (Edinburgh : Edinburgh University Press, 2022)
A collection of thought-provoking essays spanning thirty-five years of Alison Light's workProvides a historicising collection of essays, by a major critic, exemplifying and opening up feminist cultural politics to new readersOffers a way into a variety of texts and genres - including popular fiction, drama, film - as well as single authors, united by a lively and readable feminist approachExtends current thinking on national identity and Englishness from a writer who helped open these fieldsSpeaks to the new and growing academic interest in 'life-writing'Includes shorter pieces which also encapsulate complex arguments as well as examples of original life-writing by the authorIncludes an autobiographical introduction which contextualises and historicises the author's work and reflects on itAlison Light - Inside History addresses a number of the central preoccupations within feminist cultural criticism over this period: the nature of writing by women and what women writers might or might not share; the place of such writing in any literary history or cultural analysis; the politics of popular culture and the question of pleasure; women's relation to ideas of national identity and other forms of belonging; and finally, their contribution to life-writing in its different genres. The volume offers a lively, wide-ranging way into feminist debates, touching on a number of major authors from Alice Walker to Virginia Woolf, on genre fiction, and on the writing of memoir and biography. Chronologically arranged, the essays and short 'think-pieces' chart Alison Light's own intellectual formation as a critic and writer within a wider collective politics. This is explored and contextualised in an autobiographical introduction.
Frontmatter -- Contents -- Series Editors' Preface -- Acknowledgements -- Introduction: Reading Oneself Backwards -- PART I FROM FICTION TO NATION -- 1 'Returning to Manderley': Romance Fiction, Female Sexuality and Class -- 2 Fear of the Happy Ending: The Color Purple, Reading and Racism -- 3 Young Bess: Historical Novels and Growing Up -- 4 Outside History? Stevie Smith, Women Poets and the National Voice -- PART II SHORT CUTS -- 5 The Vampire and the Dog: Caryl Churchill's Mad Forest -- 6 Women Writers and Conservative Sensibilities -- 7 Against Empathy -- 8 The Mighty Mongrel: on Biography -- 9 Hitchcock's Rebecca: A Woman's Film? -- 10 Re-reading Great Expectations -- 11 The Figure of the Servant -- 12 Experiments in Memoir-writing -- PART III WRITING LIVES -- 13 A Woolf in Dog's Clothing: Flush -- 14 Fascism, Fear and Feminism: Virginia Woolf 's Three Guineas -- 15 Addicted to Diaries: The Romantic Journals of Jean Lucey Pratt -- 16 Writing the Lives of 'Common People': Reflections on the Idea of Obscurity -- Index
eBooks on EBSCOhost
Keywords: Feminist literary criticism; Women authors -- History; Feminist theory; Critique féministe.; Écrivaines -- Histoire; Théorie féministe.; LITERARY COLLECTIONS / Essays; Feminist literary criticism; Feminist theory; Women authors; History